2019
DOI: 10.1111/sjop.12513
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors at school: Reducing bullies and promoting positive bystanders' behaviors in adolescence

Abstract: Miranda, R., Oriol, X. & Amutio, A. (2019). Risk and protective factors at school: Reducing bullies and promoting positive bystanders' behaviors in adolescence. Scandinavian Journal of Psychology, 60, 106-115.Identifying protective factors present at schools located in neighborhoods with high structural violence is fundamental to help prevent the perpetuation of violence. Therefore, the aim of this study was to observe how some school micro-system variables, such as school environment and interpersonal relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 67 publications
0
11
2
1
Order By: Relevance
“…When compared to geographically close countries, involvement rates are within the expected range, although they might be considered to be medium-high [ 15 , 24 ]. When compared to the few existent studies in Peru [ 30 , 31 ], involvement in cyberbullying victimization was slightly lower in the current study. Still, in contrast to other regions of Peru, the Peruvian Amazonia is a particularly economically disadvantaged area with reduced Internet access and limited access to digital devices and smartphones.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…When compared to geographically close countries, involvement rates are within the expected range, although they might be considered to be medium-high [ 15 , 24 ]. When compared to the few existent studies in Peru [ 30 , 31 ], involvement in cyberbullying victimization was slightly lower in the current study. Still, in contrast to other regions of Peru, the Peruvian Amazonia is a particularly economically disadvantaged area with reduced Internet access and limited access to digital devices and smartphones.…”
Section: Discussioncontrasting
confidence: 88%
“…Another study, with teenagers between 12 and 17 years of age, revealed that 47% of them had been victims of violence perpetrated by peers in the past year [ 29 ]. As for cyberbullying in Peru, victimization prevalence rates of 31.3% were found [ 30 ], while other studies showed a 24.6% prevalence rate [ 31 ]. Another study, with almost one thousand Peruvian students between 9 and 11 years of age, found that between 0.7% and 3.2% of them had occasionally witnessed cyberbullying [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Note that the study was conducted with Spanish high school students with a final goal to prevent students from reproducing incivility upon their incorporation into work (Gartzia & Fetterolf, ; Miranda et al, ; Trach & Hymel, ). As derived from the results, it is necessary to be aware of the existence of stereotyped beliefs – which are probably underlying the evaluations carried out – and the mechanisms of tolerance of incivility.…”
Section: Discussionmentioning
confidence: 99%
“…To address this, and basing on Role Congruity Theory (Eagly & Karau, ), we consider future workers in a masculine context as they are relevant in order to detect early incivility that could be reproduced upon their incorporation into the labor market. This analysis could help to address the prevention of incivility as a psychosocial risk for the occupational health of female workers (Cifre, Vera & Signani, ; Cortina, Kabat‐Farr, Leskinen, Huerta & Magley, ; Miranda et al, ; Trach & Hymel, ). Thus, the aim of the present study was to examine gender differences in observers’ evaluations of the awareness and acceptability of workplace incivility gender‐dyad interaction in the male‐dominated field of engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation